Letter
010-0032-001 THE COMMUNIST PARTY OF GREAT BRITAIN (British Section of the Communist International) Read the DAILY WORKER One Penny CENTRAL COMMITTEE 16 KING STREET, COVENT GARDEN LONDON, W.C.2 Telephone: TEMple Bar 4277 ALL Communications to be addressed to THE SECRETARIAT and not to individuals 30th November, 1936. The Secretary, National Council of Labour, Transport House, Smith Square, S.W.1. Dear Comrade, You may be interested in the Resolution that was adopted unanimously at the Annual Conference of the Transvaal Provincial Labour Party held in the Trades Hall Johannesburg on November l6th. "In view of the fact that the working of the Non-Intervention Pact has resulted in arms being supplied only to the rebel Fascist forces (proceeded the resolution) this Conference strongly urges the withdrawal of the one-sided Non-Intervention Pact and requests the British Labour movement to use its best endeavours in this direction, "Resolved in their determination to defeat Fascism, the Spanish people, assisted by progressive and democratic forces of the world, will yet achieve a triumphant victory for democracy." You may be interested to know that Mr. W. Lever was in the Chair, and there were 75 delegates present, including Senator J. Briggs, Mr. W.B. Madeley,M.P., and Mr. M.J. Van der Bergh M.P. Yours fraternally, THE SECRETARIAT. 292/946/10/34